(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2011)
Extracts from natural products, especially microorganisms, have served as a valuable source of diverse molecules in many drug discovery efforts and led to the discovery of several important drugs. Identification of microbial strains having promising biological activities and purifying the bio-molecules responsible for the activities, have led to the discovery of many bioactive molecules. Extracellular, as well as intracellular, extracts of the metabolites of thirty-six bacterial and twenty-four fungal isolates, grown under unusual conditions such as high temperature, high salt and low sugar concentrations, were in vitro tested for their cytotoxic potential on various cancer cell lines. The extracts were screened on HeLa and MCF-7 cell lines to study the cytotoxic potential. Nuclear staining and flow cytometric studies were carried out to assess the potential of the extracts in arresting the cell cycle. The crude ethylacetate extract of isolate F-21 showed promising results by MTT assay with IC50 as low as 20.37±0.36 µg/mL on HeLa, and 44.75±0.81 µg/mL on MCF-7 cells, comparable with Cisplatin. The isolate F-21 was identified as Aspergillus sp. Promising results were also obtained with B-2C and B-4E strains. Morphological studies, biochemical tests and preliminary chemical investigation of the extracts were also carried out.